The Relevance of Wayang to Social Sciense Learning - AlyaRofiatus; Nur Fitria Ramadhani; Andrea Floretta Imani (Universitas Negeri Surabaya, 2024)
The purpose of this research is to analyze the development of wayang for social studies learning media. Wayang is one of the iconic arts, especially for the island of Java. The meaning and value contained in puppets can be applied in the world of education. Various kinds of values ranging from artistic value, religious value and entertainment value. The purpose of developing puppets is to determine the feasibility of developing puppets for social studies learning media and to know the history of puppet development to date. This research uses quantitative research methods where the data sought in the form of document review. The data used in the form of document review to support and strengthen this research. The results are feasible or not puppet media based on the results of trials conducted by the teacher. The results of the validity of the puppets proved to be valid. Trials conducted on students get a very good response. In this way, it is expected that puppet media can be realized in social studies learning that can be inserted into long texts. So the results of this study reveal that puppets are feasible to use as social studies learning media. It is expected that the use of puppet media can make students know and learn about the cultural arts in Indonesia, and students will be more interested so that learning will not be boring.